IMPLEMENTATION OF PROFESSIONAL ZAKAT ON ECONOMIC DEVELOPMENT AND PEOPLE'S EMPOWERMENT - Nur Dinah Fauziah; Muawanah; Moh. Suhail Wajdy Ali (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Zakat is one of the five main pillars to strengthen the religion of Islam, as a way for humans to worship Allah and also humans with other people in terms of social responsibility which can be considered as a religious tax. The zakat of the profession arises from the controversy and potential strength of the overall economy. In today's modern era, many people earn so much income by capitalizing on knowledge gained from formal education. Educational human beings can be educational systems that are programmed by the government, at least can generate enormous income compared to agricultural products, farms and plantations. Because with education gained by humans, he can have appropriate professions from the field of education that he has experienced. Therefore this writer will discuss about zakat profession which has mushroomed in this modern era. Islam aims at social unrest in society with zakat. Zakat has a mission to improve relations between human beings, which in turn can reduce the problematic gap in their lives. In addition, the Zakat can also strengthen a vertical relationship with God, because zakat is a form of devotion (worship) to the god. The ulama have determined that the property shall with zakat only five kinds, namely cattle, gold, and silver, trade, agriculture, minerals and rikaz (finding treasure). However, at present, a profession that can produce wealth is growing. Therefore, the scope of assets that zakat should be extended to some form of wealth which is not known in the early days of Islam, among other professions, doctors, notaries, bankers, psychologists, and so on.